Board of Commisioners Composition, Governance Committee, and Stock Price Synchronicity - Sansaloni Butar Butar (Jurnal Akuntansi dan Keuangan, 2019)
Market returns do not fully explain individual stock return changes, suggesting insynchronous movement between the two types of returns. The phenomena is widely called stock price synchronicity. Stock price synchronicity refers to the extent to which firm-specific information incorporated in stock prices. Prior studies suggest that price synchronicity is negatively associated with information quality. Firms with poor informational environment is likely to produce unreliable financial reports. Hence, it is a necessity for a firm to establish internal mechanisms, reflected in its corporate governance system, to promote conducive informational environment. One pillar of good corporate governance is the existence of effective Board of Commissioner. This study examines the association between Board of Commissioner composition and stock price synchronicity. Board of Commissioners composition includes Board independence, Board size, and gender diversity. In addition, this study also examine the role of Governance Committee in lowering stock price synchronicity. Regression analysis show that Board size and Board independence are negatively associated with stock price synchronicity. But no significant result were found for gender diversity. These findings suggest that larger Board size and more independent Board play significant role in improving the quality of financial reporting. And the presence of female commsioners do not affect financial reporting quality.